2017
DOI: 10.1063/1.4978376
|View full text |Cite
|
Sign up to set email alerts
|

Increased luminescence and improved decay kinetics in lithium and cerium co-doped yttrium aluminum garnet scintillators grown by the Czochralski method

Abstract: In this study, four yttrium aluminum garnet single crystals co-doped with cerium and lithium were produced by the Czochralski method and the scintillation and defect properties were investigated. Our results demonstrated an increase in luminescence with Li co-doping as well as elimination of longer decay times. Surprisingly, although Li is monovalent, no oxidation of cerium from Ce3+ to Ce4+ was found as would be expected to maintain charge neutrality. Additionally, thermoluminescence results indicated a reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 25 publications
2
15
0
Order By: Relevance
“…Only the absorption peaks corresponding to the transitions from the 4f ground state to the 5d sublevels of stable Ce 3+ ions can be identified. It suggests that Li + codoping does not introduce stable Ce 4+ ions in LSO:Ce single crystals, similar to the case of Li + codoped Y 3 Al 5 O 12 :Ce …”
supporting
confidence: 91%
See 2 more Smart Citations
“…Only the absorption peaks corresponding to the transitions from the 4f ground state to the 5d sublevels of stable Ce 3+ ions can be identified. It suggests that Li + codoping does not introduce stable Ce 4+ ions in LSO:Ce single crystals, similar to the case of Li + codoped Y 3 Al 5 O 12 :Ce …”
supporting
confidence: 91%
“…In lowly Li‐codoped LSO:Ce, Li + ions occupy both interstitial spaces and lutetium sites but prefer the former, and do not convert stable Ce 3+ to Ce 4+ . The findings of this work and the significant enhancement of light yield achieved in aluminate garnet scintillators upon Li + codoing, such as Y 3 Al 5 O 12 :Ce, Lu 3 Al 5 O 12 :Ce, and (Lu,Y) 3 Al 5 O 12 :Pr, give an indication that the effectiveness of Li codoping strategy could be general for oxide scintillators. Future work will aim at studying the concentration‐dependent effects of Li on the optical and scintillation properties of LSO:Ce, and further verify the applicability of this approach in other materials.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…One explanation for the lower light yield than that in Ref. for LuYAG:Pr is due to the fact that the actual concentration of dopant in the crystal has yet to be determined and may be less than the 0.16 at% reported to produce the light yield in Drozdowski et al Although it has been reported that lithium codoping improved light yield in cerium‐activated garnet scintillators, this is the first report of such an effect for praseodymium doped LuYAG.…”
mentioning
confidence: 67%
“…[ 22,23 ] Increased light output was observed also in YAG:Ce crystals (containing an excess of alumina) when co‐doped with Li + , while the fast decay component remained almost unchanged. [ 24 ] Ce 4+ states were not detected in X‐ray absorption spectra in LuAG:Ce,Li [ 14 ] and YAG:Ce,Li. [ 22 ] The XAS detection limit of Ce 4+ was estimated to be of the order of 13 ppm in Dickens et al [ 24 ]…”
Section: Introductionmentioning
confidence: 99%